TOURIST ATTRACTION THEME ANALYSIS OF POHSANTEN COMMUNITY-BASED TOURISM IN INDONESAIA - Ni Made Ernawati; I G P Fajar Pranadi Sudhana; Ni Made Sudarmini (P3M Politeknik Negeri Bali, 2019)
The article presents the analysis of community-based tourism attraction theme at Pohsanten village Jembrana regency Bali province in Indonesaia. This study examined the current tourist attractions themes for delivering quality CBT experience for the visitors, contributing to developing a strong theme as well as offering sufficient variety of attraction for tourists. It is a qualitative study using a combined data colleting method of interview, observation, direct participation, and documentation review from previous publication relevant to the topic. This study was conducted in conjunction with the implementation of a community service program of Politeknik Negeri Bali funded by the Directorate General of Higher Education of Indonesia. The village authority and the community members are information sources for the study, as well as the publications made earlier regarding CBT Pohsanten. Currently, CBT Pohsanten develops agrocacao, natural and cultural, and spiritual as attraction themes. The results show that having a strong and variety of tourist attractions are vital for CBT success. Nonetheless, CBT should strengthen and develop one main attraction theme whichs is the agrocacao and use the other types of attractions as supporting elements. Apart from a need to focus on one theme, CBT Pohsanten attraction is yet to be still developed and strengthened; some basic infrastructures such as pathways and resting place, toilet, meeting place, and sufficient accommodations are vital parts that influence the quality of tourist attractions and the over all CBT experiences. Keywords: community-based tourism, tourist attraction, attraction theme, unique way of life, natural environment, CBT tourist